Effectiveness of Open University Website as Administration and Academic Dissemination Media to UPBJJ-UT Mataram Students - Windi Prihandoyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to identify and analyze the effectiveness of Open University Website as administrative and academic information dissemination media to UPBJJ-UT Mataram students. The method used in this study was a descriptive correlational survey. This research was conducted at UPBJJ-UT Mataram, West Nusa Tenggara Province. Theresults indicated that student characteristics andthe quality of interaction withOpen University websitehad positive but insignificant relationship with the effectiveness of Open University website as a medium for dissemination of administrative and academic information at UPBJJ-UT Mataram. Furthermore, the usability of the Open University website and the quality of website information showed significantly positive relationship with the effectiveness of the Open University website as a medium for dissemination of administrative and academic information at UPBJJ-UT Mataram.